NO-loaded copper-based metal-organic framework material and a spray formulation for promoting wound healing
Patent Information
- Application Number
- CN202611303082.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-26
- Publication Date
- 2026-10-09
AI Technical Summary
[0005]相比之下,金属有机框架(MOFs)作为一类新兴的多孔材料,以其高结晶度、可调控孔隙率和模块化化学设计为一氧化氮储存提供了理想平台;但其生物医学应用仍受到细胞毒性和/或框架稳定性不足的制约
本发明提供一种载NO铜基金属有机框架材料,通过将不饱和金属位点及官能团(–H, –CH3, –NH2, –N(CH3)2, –C≡C–, –CONH–)整合到铜基金属有机框架材料中,获得功能化的MOFs材料,MOFs材料吸附NO后形成载NO铜基金属有机框架材料;其在一氧化氮储存与释放领域表现出优异的吸附及缓释能力;同时,材料自身具有良好的生物相容性,克服了细菌耐药性问题,这使得铜基金属有机框架材料作为NO摄取及可控释放的介导载体,具有在感染性伤口修复中的巨大应用潜力。
Smart Images

Figure CN122874607A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of metal-organic framework materials technology, and particularly to a NO-loaded copper-based metal-organic framework material and a spray formulation for promoting wound healing. Background Technology
[0002] Nitric oxide (NO) is a gaseous signaling molecule that can regulate a variety of physiological processes, including neurotransmission, cardiovascular homeostasis, immune response, and skin barrier function. In skin tissue, almost all skin cells can produce NO (even without the participation of enzymes), and it plays a key role in regulating apoptosis, keratinocyte proliferation and differentiation, immune and inflammatory responses, antibacterial activity, and wound healing.
[0003] The central role of NO in multiple signaling pathways is increasingly driving the demand for its controlled application both in vitro and in vivo. However, unlike traditional tablets or liquid formulations, gaseous NO cannot be directly administered due to its inherent physicochemical properties. Early studies primarily targeted endogenous NO synthases through gene knockout strategies or systemic drug inhibitors, but these methods cannot achieve precise spatiotemporal regulation of NO levels, leading to off-target effects and interference with important physiological functions.
[0004] In recent years, exogenous nitric oxide carriers, especially NO-loaded nanoporous materials, have been successfully designed and validated as a promising platform for the controlled and targeted delivery of NO to exert therapeutic effects. However, traditional porous materials such as activated carbon and porous ionic liquids suffer from limited storage capacity (typically <3 mmol / g), mainly due to the scarcity of NO binding sites. This inherent defect severely hinders their ability to achieve sustained and therapeutically significant nitric oxide release.
[0005] In contrast, metal-organic frameworks (MOFs), as an emerging class of porous materials, offer an ideal platform for nitric oxide storage due to their high crystallinity, tunable porosity, and modular chemical design; however, their biomedical applications are still limited by cytotoxicity and / or insufficient framework stability. These challenges highlight the urgent need to develop nitric oxide adsorbents that combine high storage capacity, good biocompatibility, and sustained release capability. Summary of the Invention
[0006] To address the problems existing in the background art, the present invention provides a NO-loaded copper-based metal-organic framework material and a spray formulation for promoting wound healing. The NO-loaded copper-based metal-organic framework material has high NO adsorption and storage capacity and continuous release capability, as well as good biocompatibility, and can be used to promote wound healing.
[0007] The specific details of the invention are as follows: In a first aspect, the present invention provides a NO-loaded copper-based metal-organic framework material, wherein the NO-loaded copper-based metal-organic framework material is formed by adsorbing NO onto the copper-based metal-organic framework material. The copper-based metal-organic framework material is formed by periodic coordination assembly of organic ligands and binuclear Cu(II) propeller secondary building units; wherein the general structural formula of the organic ligands is as follows:
[0008] Wherein, R is selected from –H, –CH3, –NH2 or –N(CH3)2, and X is selected from –C≡C– or –CONH–.
[0009] Optionally, one of the Cu(II) in the dual-core Cu(II) propeller secondary building unit is axially coordinated with the pyridine nitrogen donor in the organic ligand structure, and the other Cu(II) is axially coordinated with a water molecule, forming an open Cu(II) site after desolvation.
[0010] Optionally, the specific surface area of the copper-based metal-organic framework material is 1300 m². 2 / g-2408 m 2 / g.
[0011] Optionally, the organic ligand has the following structural formula: .
[0012] Optionally, under conditions of 298 K and 1 bar, the adsorption capacity of the copper-based metal-organic framework material for NO is 3 mmol g. -1 -10 mmol g -1 .
[0013] Optionally, under conditions of 273 K and 1 bar, the adsorption capacity of the copper-based metal-organic framework material for NO is 15 mmol g. -1 -20 mmol g -1 .
[0014] In a second aspect, the present invention provides a spray formulation for promoting wound healing, the spray formulation comprising: a liquid carrier and the NO-loaded copper-based metal-organic framework material described in the first aspect above.
[0015] Optionally, in the spray formulation for promoting wound healing, the NO-loaded copper-based metal-organic framework material and the liquid carrier are independently packaged in different chambers of the spray device. During use, the NO-loaded copper-based metal-organic framework material and the liquid carrier are mixed and sprayed out by pressing the pump head.
[0016] Optionally, the liquid carrier includes deionized water.
[0017] Optionally, the concentration of the NO-loaded copper-based metal-organic framework material is 50 μg / mL-200 μg / mL. Compared with the prior art, the present invention has the following advantages: This invention provides a NO-loaded copper-based metal-organic framework (MOF) material. By integrating unsaturated metal sites and functional groups (–H, –CH3, –NH2, –N(CH3)2, –C≡C–, –CONH–) into a copper-based MOF material, a functionalized MOF material is obtained. After adsorbing NO, the MOF material forms a NO-loaded copper-based MOF material. It exhibits excellent adsorption and sustained-release capabilities in the field of nitric oxide storage and release. At the same time, the material itself has good biocompatibility, overcoming the problem of bacterial resistance. This makes the copper-based MOF material a promising candidate for NO uptake and controlled release in the repair of infected wounds. Attached Figure Description
[0018] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0019] Figure 1 The organic ligand H4L is shown in an embodiment of the present invention. 4 Flowchart of the preparation process; Figure 2 The PXRD data comparison between the simulated material (black) and the actual synthesized material (red) in the embodiments of the present invention is shown; Figure 3 Three cage-like structures in MFM-170 material, as determined by X-ray diffraction, are shown. Figure 4 The cage-like B structure and binding site structure in a series of isomorphic MOF materials, as determined by X-ray diffraction, are shown. Figure 5 The cage-like C and binding site structures in a series of isomorphic MOF materials, as determined by X-ray diffraction, are shown. Figure 6 The TGA curves of a series of isomorphic MOFs materials in embodiments of the present invention are shown; Figure 7 The NO adsorption experimental results of a series of isomorphic MOFs materials in the embodiments of the present invention are shown; Figure 8The antibacterial activity of the MOF material provided in the embodiments of the present invention against Escherichia coli and methicillin-resistant Staphylococcus aureus at different concentrations is shown. Figure 9 The evolution of resistance to Escherichia coli and Staphylococcus aureus by NO@MFM-174 provided in the embodiments of the present invention is shown under sub-minimum inhibitory concentration conditions. Figure 10 The results of cell compatibility and cell behavior regulation were shown; Figure 11 A schematic diagram of a dual-chamber spray device is shown; Figure 12 The study demonstrated the antibacterial and wound-healing effects of NO@MFM-174 in vivo. Detailed Implementation
[0020] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. The following description of at least one exemplary embodiment is merely illustrative and is in no way intended to limit the present invention or its application or use. Based on the embodiments of the present invention, any product that is the same as or similar to the present invention, derived by anyone under the guidance of the present invention or by combining the features of the present invention with other prior art, falls within the protection scope of the present invention. Furthermore, all other embodiments obtained by those skilled in the art without inventive effort are within the protection scope of the present invention.
[0021] Specific experimental steps or conditions are not specified in the embodiments; they can be performed according to the conventional experimental steps or conditions described in the prior art. Reagents and other instruments used, unless otherwise specified, are all commercially available conventional reagent products. Furthermore, the accompanying drawings are merely illustrative diagrams of the embodiments of the present invention and are not necessarily drawn to scale. The same reference numerals in the drawings denote the same or similar parts, and therefore, repeated descriptions of them will be omitted. Some block diagrams shown in the drawings are functional entities and do not necessarily correspond to physically or logically independent entities.
[0022] Techniques, methods, and devices known to those skilled in the art may not be discussed in detail, but where appropriate, such techniques, methods, and devices should be considered part of this specification.
[0023] Furthermore, the technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0024] In a first aspect, the present invention provides a NO-loaded copper-based metal-organic framework material, wherein the NO-loaded copper-based metal-organic framework material is formed by adsorbing NO onto the copper-based metal-organic framework material. The copper-based metal-organic framework material is formed by periodic coordination assembly of organic ligands and binuclear Cu(II) propeller secondary building units; wherein the general structural formula of the organic ligands is as follows:
[0025] Wherein, R is selected from –H, –CH3, –NH2 or –N(CH3)2, and X is selected from –C≡C– or –CONH–.
[0026] In practical implementation, the structure of the organic ligand is as follows:
[0027] In this embodiment, H4L 1 H4L 2 H4L 3 H4L 4 H4L 5 and H4L 6 respectively with Cu 2+ Coordination assembly was used to form copper-based metal-organic framework (MOF) materials MFM-170, MFM-172, MFM-174, PKU-177, NJU-Bai 20 and NJU-Bai 21 (obtained by periodic coordination assembly of organic ligands and binuclear Cu(II) propeller secondary building blocks).
[0028] Furthermore, the NO loading and adsorption of copper-based metal-organic frameworks (MOFs) is based on the synergistic chemical interaction of the framework structure, open metal sites, and ligand functional groups. In the pristine state (without the introduction of functional groups R), one of the Cu(II) atoms in the binuclear propeller unit is axially coordinated with bound water molecules. After solvent removal and activation, the coordinated water molecules are removed, exposing an open unsaturated Cu(II) site. NO molecules preferentially undergo strong coordination with this unsaturated copper site, accompanied by charge transfer between the framework and NO, thereby disrupting the Cu... 2+The antiferromagnetic coupling within the propeller unit enables the chemical binding of NO, unlike ordinary physical adsorption. When organic ligands introduce functional groups such as amino groups, the amino group can act as a second type of binding site, undergoing an addition chemical reaction with NO, further enhancing the NO capture capacity. The interconnected A, B, and C cage-like cavities within the crystal provide sufficient space. Driven by the synergistic effect of open Cu(II) sites and amino functional groups, NO molecules can be densely packed and enriched within the cages, achieving large-capacity NO storage. Subsequent characterization by neutron powder diffraction, in-situ infrared spectroscopy, and electron paramagnetic resonance confirmed that NO adsorption does not damage the MOF crystal framework. When the NO-loaded copper-based metal-organic framework (MOF) material comes into contact with an aqueous medium, the Cu-NO coordination is weakened by disturbance, and the bound NO can be gradually released, thus completing the entire process of nitric oxide storage and controlled slow release.
[0029] In specific implementation, after the load on MFM-170 is NO, it is marked as NO@MFM-170; after the load on MFM-172 is NO, it is marked as NO@MFM-172; after the load on MFM-174 is NO, it is marked as NO@MFM-174; after the load on PKU-177 is NO, it is marked as NO@PKU-177; after the load on NJU-Bai 20 is NO, it is marked as NO@NJU-Bai 20; after the load on NJU-Bai 21 is NO, it is marked as NO@NJU-Bai21.
[0030] Secondly, the present invention provides a spray formulation for promoting wound healing. The spray formulation comprises: a liquid carrier and the NO-loaded copper-based metal-organic framework material described in the first aspect.
[0031] In practice, in the spray formulation that promotes wound healing, the NO-loaded copper-based metal-organic framework material and the liquid carrier are independently packaged in different chambers of the spray device. When in use, the NO-loaded copper-based metal-organic framework material and the liquid carrier are mixed and sprayed out by pressing the pump head.
[0032] In practice, the liquid carrier is deionized water.
[0033] In specific implementation, the concentration of the NO-loaded copper-based metal-organic framework material is 50 μg / mL-200 μg / mL.
[0034] The following will provide a detailed introduction to the contents of the first and second aspects mentioned above: See Figure 1 The organic ligand shown (H4L) 4 Flowchart of the preparation process: Step 1: 4-Bromophenylboronic acid (3.11 g, 15.5 mmol) and 1,8-diaminonaphthalene (2.69 g, 17 mmol) were dissolved in toluene (250 mL) and refluxed at 120 °C for 2 hours in a single-necked flask. The solvent was then removed by rotary evaporation, and the mixture was recrystallized from dichloromethane and a mixture of n-hexane and petroleum ether to give pink needle-like crystals, namely compound (2) (chemical structure shown in [reference needed]). Figure 1 (as shown in (2)). 1 The H NMR spectrum is as follows: 1 H NMR (400 MHz, CDCl3) δ ppm 7.61 (2 H, m), 7.54(2 H, m), 7.18 (2 H, m), 7.10 (2 H, m), 6.45 (2H, dd), 6.00 (2H, br s).
[0035] Step 2: Compound (2) (2.25 g, 6.95 mmol) and diethyl 3,5-phenylboronic acid (chemical structure shown in [link to article]) were added. Figure 1 The compound (1) (2.80 g, 10.4 mmol) and potassium carbonate (2.85 g, 20.5 mmol) were dissolved in toluene / water solution (225 mL, volume ratio 4:1) and degassed at 45 °C. Xphos (476.5 mg, 1 mmol) and Pd2(dba)3 (415 mg, 0.5 mmol) were added, and the reaction mixture was heated to 80 °C for 2 hours. The mixture was then filtered through diatomaceous earth, and the organic phase was collected. After removing the solvent by vacuum distillation, the residue was sonicated in methanol for half an hour and filtered to obtain the solid product, namely compound (3) (chemical structure shown in [reference]). Figure 1 (as shown in (3)) and dried. 1 The H NMR spectrum is as follows: 1 H NMR (400MHz, CDCl3)δ ppm: 8.70 (1H, s), 8.52 (2H, s), 7.78 (4H, m), 7.10 (2H, m),7.18 (2H, t, J = 8.28 Hz), 7.10 (2H, d, J = 8.16 Hz) 6.46 (2H, d, J = 7.20Hz), 6.11 (2H, br s), 4.48 (4H, q, J = 7.1 Hz), 1.47 (6H, t, J = 7.1 Hz).
[0036] Step 3: Compound (3) (2.12 g, 4.6 mmol) was dissolved in a mixed solution of tetrahydrofuran (150 mL) and sulfuric acid (2 M, 25 mL). The solution was refluxed overnight at 80 °C, the precipitate was removed by filtration, THF was removed by rotary evaporation, and water was added to the solution to precipitate the product, yielding a light brown powder, namely compound (4) (chemical structure shown in [link to compound (4)]). Figure 1 (as shown in (4)). 1 The H NMR spectrum is as follows: 1 H NMR (400 MHz, DMSO-d6) δ ppm: 8.44 (3H, d, J = 17.4 Hz), 8.16 (2H,br s), 7.95 (2H, d, J = 7.7 Hz), 7.73 (2H, d, J = 7.6 Hz), 4.40 (4H, q, J =7.1 Hz), 1.38 (6H, t, J = 7.1 Hz).
[0037] Step 4: 0.6 g (1.75 mmol) of compound (4), 0.16 g (0.572 mmol) of dibromopyridine intermediate (3,5-dibromo(pyridin-4-yl)dimethylamine) (0.16 g, 0.572 mmol), and 0.85 g (1.8 mmol) of potassium carbonate were dissolved in a THF:water solution (100 mL, volume ratio 5:1) and degassed at 45 °C. Pd(PPh3)4 (51.95 mg, 0.025 mmol) was added, and the reaction was heated at 80 °C for two days. The product was extracted with dichloromethane, the solvent was removed under vacuum, and then recrystallized from dichloromethane with ethanol to obtain a pale white powder. 1 The H NMR spectrum is as follows: 1 H NMR (400 MHz, CDCl3) δ ppm: 8.69 (2H, t, J = 1.56Hz), 8.52 (4H, d, J = 1.60 Hz), 8.34 (2H, s), 7.80 (4H, d, J = 8.44 Hz), 7.50(4H, d, J = 8.44 Hz), 4.47 (8H, q, J = 7.24 Hz), 2.47 (6H, s), 1.46 (12H, J =7.08 Hz).
[0038] Step 5: Dissolve the product obtained in Step 4 in a mixed solution of sodium hydroxide (2 M, 50 mL), THF (25 mL), and ethanol (25 mL), and stir at 90 °C for 4 hours. After removing the organic solvent, acidify the aqueous solution with hydrochloric acid (2 M) until a white solid precipitates, namely compound (6) (chemical structure shown in [reference needed]). Figure 1 As shown in (6), it is labeled H4L 4 (Yield 0.197 g, calculated value 57.2%, obtained from step (4)); 1 The H NMR spectrum is as follows: 1 H NMR (400 MHz, DMSO-d6) δppm:13.43 (4H, s), 8.50 (2H, t, J = 1.72 Hz), 8.47 (4H, d, J= 1.56 Hz), 8.34(2H, s), 7.91 (4H, d, J = 8.44 Hz), 7.60 (4H, d, J = 8.28 Hz), 2.41 (6H, s).
[0039] The preparation of the dibromopyridine intermediate (3,5-dibromo(pyridin-4-yl)dimethylamine) was as follows: 3,5-dibromo-4-chloropyridine (2.69 g, 10 mmol) was mixed with dimethylamine (33% aqueous solution, 27 mL, 22 mmol), and heated at 118 °C for 20 hours in a sealed pressure tube. The reaction mixture was then cooled to room temperature and extracted three times with ethyl acetate (3 times, 50 mL each time). The combined extracts were washed with 1 M potassium carbonate (2 × 30 mL) and deionized water (2 × 30 mL). The organic layer was dried over magnesium sulfate and evaporated under vacuum to obtain white 3,5-dibromo(pyridin-4-yl)dimethylamine crystals (2.43 g, yield 87%). (H NMR spectroscopy is described below.) 1 ¹H NMR (400 MHz, CDCl₃) δ ppm: d: 8.48 (s, 2H), 2.99 (s, 6H); The reaction formula is shown below: .
[0040] As can be seen from the structural formula of the organic ligand, H4L 1 H4L 2 H4L 3 and H4L 4 The only difference is that different functional groups are modified at the 4-position of the intermediate pyridine ring; that is, the synthesis of H4L 1 H4L 2 H4L 3 With the synthesis of H4L 4 The main difference lies in the choice of different dibromopyridine intermediates; among them, the synthesis of H4L 1 The selected dibromopyridine intermediate was 3,5-dibromopyridine; H4L was synthesized. 2 The selected dibromopyridine intermediate was 3,5-dibromo-4-methylpyridine; H4L was synthesized. 3The selected dibromopyridine intermediate is 3,5-dibromo-4-aminopyridine.
[0041] Furthermore, H4L 5 The synthesis method is as follows: Dimethyl-5-iodoisophthalate (2.010 g, 6.25 nmol), Pd(PPh3)2Cl2 (0.0439 g, 0.063 mmol), and CuI (0.0238 g, 0.125 mmol) were added to anhydrous triethylamine solvent (40 mL). The resulting mixture was stirred at room temperature for 10 min, followed by the addition of 3,5-ethynylpyridine powder (0.406 g, 3.20 mmol). The reaction mixture was stirred at room temperature for 16 h. The solvent was removed by vacuum distillation, and the resulting solid was redissolved in 50 mL of dichloromethane. The organic phase was washed with water and dried over anhydrous Na2SO4. Volatile substances were removed by vacuum distillation, yielding 1,3-bis(3,5-dicarboxyphenylethynyl)pyridine tetramethyl ester, which, after drying, was a white powder (1.030 g, yield 63.3% based on dimethyl 5-iodoisophthalate). Potassium hydroxide (2.53 g, 47.0 mmol) was dissolved in 50 mL of methanol. Then, 1,3-bis(3,5-dicarboxyphenylethynyl)pyridine tetramethyl ester (1.030 g, 2.028 mmol) was added, and the mixture was stirred overnight at 80 °C. Volatile substances were removed by vacuum evaporation. The residue was dissolved in water, filtered, and the pH was adjusted to ~2-3 with dilute hydrochloric acid while stirring to precipitate the product. The resulting precipitate was collected by filtration, washed with water, and dried to give 1,3-bis(3,5-dicarboxyphenylethynyl)pyridine (L) (H4L). 5 (0.8657 g, yield 94.1%). Hydrogen nuclear magnetic resonance (HNMR) spectrum (400 MHz, DMSO-d6): 13.41 δ ppm: 13.41 (s, 4H), 8.87 (s, 2H), 8.49 (s, 2H), 8.37 (s, 1H), 8.32 (s, 4H).
[0042] Furthermore, H4L 6 The synthesis method is as follows: In a 250 mL round-bottom flask, anhydrous pyridine-3,5-dicarboxylic acid (2.0 g, 12.0 mmol) and thioyl chloride (40.0 mL, 0.55 mol) were added. Then, N,N-dimethylformamide (1.0 mL, 12.9 mmol) was added dropwise. The mixture was stirred and heated to 75°C for 6 hours under a nitrogen atmosphere. After removing excess SOCl2 by aeration, the mixture was quenched with ethanol and water to obtain pyridine-3,5-dicarbonyl chloride (which can be used directly without further purification).
[0043] The obtained pyridine-3,5-dicarbonyl chloride (0.61 g, 3.0 mmol) was dissolved in anhydrous acetonitrile (20 mL), and then a solution of 5-aminoisophthalic acid (1.27 g, 7.0 mmol) in acetonitrile (20 mL) was added dropwise. The resulting mixture was stirred at room temperature for 24 hours, followed by reflux for 2 hours. The precipitated white solid was separated by filtration and washed with fresh acetonitrile (50 mL) and water (300 mL) to finally obtain 5,5'-((pyridine-3,5-diyl)bis(azadiethylenedimethyl))diisophthalic acid (H4L) 6 The sample was dried overnight under vacuum (<0.1 mmHg) (1.27 g, total yield 86%). Hydrogen nuclear magnetic resonance (H-NMR) spectra (400 MHz, DMSO-d6) δ ppm: 10.96 (s, 2 H), 9.33 (d, 2 H), 8.94 (t, 1 H), 8.72 (d, 4 H), 8.26 (t, 2 H).
[0044] Furthermore, H4L 4 10 mg (0.17 mmol) and Cu(NO3)2·3H2O (18.6 mg, 0.08 mmol) were dissolved in N,N-dimethylformamide solution (3 mL), and acidified with three drops of concentrated nitric acid. The solution was heated to 80 °C for two days, after which blue-green crystals precipitated. The product was filtered, washed with hot N,N-dimethylformamide, and exchanged with acetone. The copper-based metal-organic framework (MOF) material PKU-177 was finally obtained.
[0045] Furthermore, using a synthesis method similar to PKU-177, H4L 1 H4L 2 H4L 3 H4L 5 and H4L 6 respectively with Cu 2 + Coordination assembly can yield copper-based metal-organic framework (MOF) materials MFM-170, MFM-172, MFM-174, NJU-Bai 20, and NJU-Bai 21.
[0046] Structural and property characterization of copper-based metal-organic frameworks (MOFs): (1) Powder X-ray diffraction Powder X-ray diffraction (PXRD) data in the range of 5–35° were acquired using an X'Pert3 powder diffractometer in planar mode under Cu-Kα radiation (λ = 1.5418 Å) at 40 kV and 40 mA. (See also: [link to PXRD data]) Figure 2 A comparison of PXRD data of the simulated material (black) and the actual synthesized material (red) shows that the measured 2θ position of the diffraction peak corresponds well with the simulated diffraction peak of the corresponding single crystal structure, with no obvious shift. This indicates that the synthesized isomorphic MOFs materials (MFM-170, MFM-172, MFM-174, PKU-177, NJU-Bai 20, NJU-Bai 21) are consistent with their theoretical target crystal phase, and the expected crystal phase has been successfully obtained.
[0047] Furthermore, Figure 3 Three cage-like structures in MFM-170 material, as determined by X-ray diffraction, are shown. Figure 4 The cage-like B structure and binding site structure in a series of isomorphic MOF materials, as determined by X-ray diffraction, are shown. Figure 5 This illustrates the cage-like C and binding site structures in a series of isomorphic MOF materials, as determined by X-ray diffraction; from Figures 3-5 As can be seen from the diagram (C: gray; O: red; Cu: cyan; N: blue), MFM-170, MFM-172, MFM-174, PKU-177, NJU-Bai 20, and NJU-Bai 21 are isomorphic frameworks constructed by the coordination of binuclear Cu(II) propeller secondary building units with pyridyltetracarboxylic acid ligands. The crystal interior forms cage-like cavities of three alternating stacks of A, B, and C that are interconnected. Cage A maintained a consistent structure and size (15.1 Å) across all samples. Cage C had a size of 8.0 × 11.7 Å in MFM-17X and PKU-177, and 9.8 × 9.6 Å and 8.7 × 7.2 Å in NJU-Bai20 and NJU-Bai21, respectively. Cage B was an elliptical cavity whose volume gradually decreased with increasing volume of the pyridine nitrogen para-substituents (–CH3, –NH2, –N(CH3)2). The exposed amino and dimethylamino functional groups on the inner wall served as NO binding sites. In the copper-based MOFs material provided in this embodiment, one Cu(II) in the binuclear Cu(II) propeller secondary building block is axially coordinated with the pyridine nitrogen donor in the organic ligand structure, while the other Cu(II) is axially coordinated with water molecules, forming open Cu(II) sites after desolvation.
[0048] (2) Thermogravimetric analysis The thermal stability of MOF materials was determined using a thermogravimetric analyzer (SDT650, TA Instruments). Approximately 2 mg of the sample was placed in a reaction dish and heated from room temperature to 800 °C at a heating rate of 10 °C / min under airflow, followed by cooling to room temperature. See [link to relevant documentation]. Figure 6The TGA curves show that the thermal behavior of all MOF materials exhibits similar patterns: from room temperature to 200 °C, the main process involves the removal of pore solvent and coordinated water molecules; a clear thermal stability plateau appears in the 200–300 °C range, proving that the framework of this series of MOFs can be stable above 300 °C, demonstrating good thermal stability. Above 300 °C, the coordination nodes of organic and metal ligands gradually undergo oxidative decomposition, resulting in rapid weight loss; at 800 °C, the final residue is an inorganic oxide of copper. Different pyridine ring substituents only slightly affect the decomposition temperature of the organic components and do not significantly reduce the overall thermal stability of the materials.
[0049] (3) Specific surface area (BET) measurement After being dried in air, the acetone-substituted MOF materials were subjected to a 10-day incubation period at 150 °C. -10 Completely desolventized samples were obtained after treatment under bar conditions for 12 hours, and their porosity was subsequently characterized using a 3-flex instrument (Micrometrics). BET was calculated using N2 isotherm data measured at 77 K. The test results showed that the specific surface areas of the desolventized MFM-170, MFM-172, MFM-174, PKU-177, NJU-Bai 20, and NJU-Bi 21 were 2408, 1978, 2251, 1832, 1933, and 1300 m², respectively. 2 / g.
[0050] (4) NO isothermal adsorption Using a turbopump system, in ultra-high vacuum (10 -10 The gravimetric adsorption isotherm of NO was recorded using a Hiden XEMIS system under dynamic high vacuum conditions (bar). Ultrapure research-grade (99.95%) NO used in the experiment was purchased from Air Liquide. In a typical gas adsorption experiment, acetone-substituted MOF material (30 mg) was loaded into the XEMIS system and subjected to dynamic high vacuum (pump pressure reading 10 bar). -10 The sample was activated at 423 K for 12 hours under pressure conditions (bar) to obtain a completely desolvated sample. The sample was then cooled to 298 K in a vacuum environment and exposed to NO gas for adsorption measurements within a pressure range up to 1 bar. Adsorption isotherms were collected by gravimetric method, and data points were recorded after each pressure step was equilibrated.
[0051] See Figure 7 The results of the isothermal NO adsorption experiment are shown. Figure 7a) shows the NO adsorption capacity of Cu-based MOFs materials under conditions of 298 K and 1 bar. The NO adsorption capacities of MFM-170, MFM-172, PKU-177, NJU-Bai 20, and NJU-Bai 21 were 4.67, 4.58, 3.32, 4.98, and 5.40 mmol g, respectively. -1 In contrast, MFM-174 exhibited extremely high NO adsorption capacity (9.39 mmol g) at 298 K and 1 bar. -1 The adsorption capacity increased significantly at 50 mbar, exhibiting a stepwise adsorption behavior, indicating that the introduction of amino groups greatly enhanced the NO packing density within the pores. Figure 7 As can be seen from b, the adsorption behavior of MFM-174 shows a consistent trend at different temperatures, and the material achieves an adsorption capacity as high as 19.38 mmol g at 273 K and 1 bar. -1 NO adsorption capacity; from Figure 7 As can be seen from d, the packing density of MFM-174 at 273 K and 1 bar is as high as 0.72 g cm⁻¹. -3 It exhibits higher NO adsorption capacity and bulk density than other reported porous materials. Based on the excellent NO adsorption performance of MFM-174, Figure 7 Further evaluation was conducted on the gas release capacity and release kinetics of NO@MFM-174 under physiological conditions. Notably, NO@MFM-174 exhibited a significant time-dependent release characteristic, with a cumulative release of 350 μM within 4 hours, a concentration within the ideal range for antibacterial efficacy. In contrast, the release curve of NO@MFM-170 was significantly flatter, indicating a different nitric oxide release mechanism, consistent with its adsorption isotherm characteristics.
[0052] (5) Antibacterial test To evaluate the antibacterial activity of different MOF materials, four dispersions (MFM-170, NO@MFM-170, MMF-174, and NO@MFM-174, with final concentrations of 25, 50, 100, 200, and 400 μg / mL, respectively) were prepared and co-incubated with bacterial suspensions; PBS was used as a negative control. After 2 hours of co-incubation, the bacterial suspensions were serially diluted 100-fold with PBS, and 100 μL samples were plated on BHI agar plates and incubated overnight at 37°C; representative colony images were taken the following day.
[0053] Figure 8 The antibacterial activity of the MOFs material provided in the embodiments of the present invention against *Escherichia coli* and methicillin-resistant *Staphylococcus aureus* (MRSA) at different concentrations is shown, such as... Figure 8As shown, pure MFM-170 and MFM-174 exhibited weak antibacterial effects against the two pathogenic bacteria. NO@MFM-170 showed good antibacterial activity against MRSA, effectively inhibiting MRSA at concentrations ranging from 50 μg / mL to 200 μg / mL, but showing weak antibacterial effect against Escherichia coli. NO@MFM-174, on the other hand, exhibited excellent broad-spectrum antibacterial activity, with a concentration-dependent antibacterial effect, effectively inhibiting bacteria at concentrations ranging from 50 μg / mL to 200 μg / mL, and completely eliminating both pathogenic bacteria at a concentration of 200 μg / mL. These results confirm that the antibacterial activity of this material is mainly mediated by sustained-release nitric oxide, and the MOF backbone itself has no significant bactericidal effect.
[0054] (6) Bacterial resistance induction assay The changes in the minimum inhibitory concentration (MIC) of Staphylococcus aureus and Escherichia coli under long-term exposure to 0.25 times the minimum inhibitory concentration (MIC) of NO@MFM-174 were monitored using a sequential subculturing method. The specific procedure was as follows: Staphylococcus aureus and Escherichia coli were inoculated into BHI broth and cultured to the logarithmic growth phase, then diluted with PBS to approximately 1×10⁻⁶. 5 CFU / mL; then, the bacteria were exposed to NO@MFM-174 concentrations below the MIC value, with gentamicin and vancomycin added as positive controls. All bacterial cultures were incubated at 37°C with shaking at 200 rpm for 24 hours, and the MIC value was measured (incubation time set to 16 hours). During continuous passage, bacteria that remained viable at the highest drug concentration were collected and re-inoculated into fresh medium containing the corresponding subMIC concentration of NO@MFM-174 or antibiotic for the next round of passage. This process was repeated for 20 days, and the MIC values for NO@MFM-174, gentamicin, and vancomycin were recorded daily to assess the development of bacterial resistance. To further assess the stability of the resistance phenotype, after 20 days of continuous passage, the bacteria were transferred to fresh medium without antibiotics and cultured for another 4 days, after which antibiotics were discontinued, and the MIC value was measured again.
[0055] Figure 9 The diagram illustrates the evolution of resistance to *Escherichia coli* (left) and *Staphylococcus aureus* (right) by NO@MFM-174 provided in this embodiment of the invention under minimum inhibitory concentration (sub-MIC) conditions. Figure 9 As shown, the MIC of NO@MFM-174 for both bacteria did not increase significantly, indicating that this material hardly induces bacterial resistance. In contrast, gentamicin significantly increased bacterial resistance levels, and vancomycin also exhibited varying degrees of resistance. This difference stems from the multi-target antibacterial mechanism of NO, which differs from the single-target action of traditional antibiotics, confirming that NO@MFM-174 carries a lower risk of resistance with long-term use.
[0056] (7) Cell compatibility assessment L929 mouse fibroblasts were cultured in DMEM medium supplemented with 10% fetal bovine serum (FBS) and 1% penicillin-streptomycin under standard culture conditions (37°C, 5% CO2). The medium was changed every 1–2 days. When the cell confluence reached approximately 80%, the cells were washed with sterile PBS and passaged using 0.25% trypsin-EDTA for subsequent experiments. For live / dead cell staining experiments, L929 cells were cultured at 2 × 10⁶ cells per well. 4 L929 cells were seeded at a density of 100, 200, and 300 μg / mL in 24-well plates and cultured for 24 hours to promote cell adhesion. Then, MFM-170, NO@MFM-170, MFM-174, and NO@MFM-174 were added at concentrations of 100, 200, and 300 μg / mL, respectively, with PBS as a control. After 24 hours of incubation, the culture medium was removed, and the cells were gently washed three times with PBS. Cells were stained using the Calcein-AM / PI live / dead cell staining kit according to the manufacturer's instructions and incubated in the dark for 20-30 minutes. Fluorescence images were then acquired using a fluorescence microscope: green fluorescence represented live cells, and red fluorescence represented dead cells. For CCK-8 assays, L929 cells were seeded at a density of 2 × 10⁶ cells / well. 4 Cells were seeded at a density of [number] cells per well in 96-well plates and cultured for 24 hours. Subsequently, cells were treated with MFM-170, NO@MFM-170, MFM-174, and NO@MFM-174 at concentrations of 12.5, 25, 50, 100, 200, and 300 μg / mL, respectively. The PBS-treated group served as a control. After 24 hours of culture, the medium was replaced with fresh medium containing 10% CCK-8 reagent, and the cells were cultured for another 2 hours. The absorbance was measured at 450 nm using a microplate reader.
[0057] Figure 10 The results of cell compatibility and cell behavior regulation are shown, in which, Figure 10 a shows the live / dead staining results of L929 fibroblasts after treatment with different concentrations of materials. The results indicate that MFM-174 and NO@MFM-174 have good biosafety. Figure 10 b shows the CCK-8 assay results of L929 cells under different material treatments. The results indicate that NO@MFM-174 has the dual advantages of low toxicity and promoting cell proliferation. Figure 10 c represents the accumulation of copper from the material source in L929 fibroblasts after treatment with the Cu-based MOFs materials of this embodiment. The analysis of intracellular copper content shows that the MFM-174 skeleton is more stable, and copper ions are not easily dissolved and taken up by cells, effectively avoiding cell damage caused by metal ions. Figure 10 d and Figure 10e represents the migration behavior of L929 fibroblasts after treatment with Cu-based MOFs materials in this embodiment. Data are expressed as mean ± standard deviation, n ≥ 3. p<0.05, p<0.01, p<0.001; Experimental results confirmed that NO@MFM-174 can significantly accelerate the migration rate of L929 cells. Figure 10 The experimental results of the reaction show that the amino-modified MFM-174 substrate has good biocompatibility, and its loaded and sustained-release nitric oxide can effectively promote fibroblast proliferation and migration, providing a favorable cellular basis for the repair of infected wounds.
[0058] (8) Spray design Nitric oxide (NO) is sensitive to air and is released upon contact with water. To address this issue, this invention develops a dual-chamber spray system equipped with a powder-liquid separation device; see [link to related document]. Figure 11 The schematic diagram of the dual-chamber spray device shows that the MOF material carrying NO is encapsulated in the upper chamber, while the solvent used to trigger NO release is stored in the lower chamber, maintaining strict separation until use. During operation, pressing the actuator lowers the bottom of the upper chamber, opening the chamber and allowing the two components to mix thoroughly through vibration, thus forming a ready-to-use homogeneous dispersion.
[0059] (9) Evaluation of NO@MFM-174 in vivo wound healing and biosafety The in vivo wound healing effect of NO@MFM-174 was evaluated using a mouse MRSA-infected full-thickness resection wound model. The procedure strictly adhered to institutional animal care and usage guidelines. BALB / c mice underwent acclimatization training before the experiment and were randomly assigned to different treatment groups (n=3 per group). Body weight and overall physiological status were monitored daily throughout the experiment. After intraperitoneal anesthesia, the fur on the back of the mice was removed and the skin was disinfected. A full-thickness circular resection wound with a diameter of approximately 5 mm was created on the back skin. Subsequently, 10 μL of MRSA suspension (1×10⁻⁶) was inoculated into each wound area. 8A wound model of infection was established by covering the wound with sterile 3M breathable tape for 24 hours (CFU / mL). After model establishment, mice were randomly assigned to PBS, MFM-174, and NO@MFM-174 treatment groups, with different formulations sprayed onto the wound (PBS served as a blank control). Wound images were taken and the wound area measured on days 3, 5, and 7 to assess wound closure and wound edge contraction. Mice were sacrificed on day 7 after treatment, and wound tissue samples, including adjacent normal skin, were collected. Major organs such as the heart, liver, spleen, lungs, and kidneys were also collected for biosafety assessment. The collected tissue samples were fixed, embedded in paraffin, and sectioned into 3 μm thick sections, followed by standard hematoxylin and eosin (H&E) staining and Masson's trichrome staining. Histological images were obtained using an optical microscope.
[0060] See Figure 12 The in vivo antibacterial effect and wound healing effect are shown, among which Figure 12 a is a schematic diagram of the MRSA-infected mouse wound model and treatment process; Figure 12 b shows representative images of wound healing progress at different time points (days 3, 5, and 7) after treatment with the control group, MFM-174, and NO@MFM-174. Figure 12 c represents the quantitative analysis of wound closure rate; Figure 12 d represents the histological analysis of wound tissue performed using H&E staining and Masson's trichrome staining. Data are expressed as mean ± standard deviation, n ≥ 3. p<0.05, p<0.01, p<0.001; such as Figure 12 As shown, the process of modeling, inoculation with drug-resistant bacteria, spray drug administration, and dynamic observation were completed according to the preset procedure. Figure 12 a). Macroscopic images of the wound showed that, with prolonged treatment time, the wound contraction rate in the NO@MFM-174 group was significantly better than that in the control group and the MFM-174 group, and the wound was basically completely healed by day 7; quantitative data on wound closure rate further confirmed that its in vivo healing-promoting effect had a highly significant difference. Figure 12 b、 Figure 12 c). H&E staining showed that NO@MFM-174 could effectively inhibit wound inflammation, reduce inflammatory cell infiltration, and protect normal tissue; Masson trichrome staining results confirmed that this material could significantly promote collagen fiber deposition and accelerate granulation tissue maturation and tissue remodeling. Figure 12d) No obvious pathological damage was observed in the pathological sections of major organs, proving that the topical application of this spray is safe. Combined with in vitro experiments, it can be seen that NO@MFM-174 achieves multiple effects such as potent killing of drug-resistant bacteria, inhibition of inflammation, regulation of fibroblast behavior, and promotion of collagen synthesis by relying on the controlled release of nitric oxide, and has good application prospects in the clinical treatment of wounds infected by drug-resistant bacteria.
[0061] In summary, this invention integrates unsaturated metal sites and functional groups (–H, –CH3, –NH2, –N(CH3)2, –C≡C–, –CONH–) into copper-based metal-organic frameworks (MOFs) and elucidates their roles in nitric oxide storage and release. Among these, the amino-functionalized MOF material MFM-174 exhibits excellent nitric oxide adsorption capacity of 19.4 mmol g at 273 K and 1 bar. -1 MFM-174 is the most efficient NO adsorbent reported to date. Crystallographic, spectroscopic, and density functional theory simulations show that unsaturated copper sites act as the primary NO binding sites, while amino groups promote rapid NO adsorption. The NO-rich environment formed by these primary sites encourages dense NO arrangement within the pores. Notably, MFM-174 combines the ability to continuously release NO with excellent biocompatibility, fully meeting the core requirements of an ideal NO-releasing biomedical material. In vitro antibacterial experiments validated its effectiveness and overcame bacterial resistance issues; in vivo wound healing experiments further confirmed its therapeutic effect in a mouse model. Based on these positive results, a portable NO@MFM-174 spray device was developed, significantly enhancing its clinical application potential.
[0062] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. In addition, those skilled in the art can combine and integrate the different embodiments or examples described in this specification.
[0063] For the sake of simplicity, the method embodiments are described as a series of actions. However, those skilled in the art should understand that the present invention is not limited to the described order of actions, as some steps can be performed in other orders or simultaneously according to the present invention. Furthermore, those skilled in the art should also understand that the embodiments described in the specification are preferred embodiments, and the actions and components involved are not necessarily essential to the present invention.
[0064] The foregoing has provided a detailed description of the NO-loaded copper-based metal-organic framework material and the spray formulation for promoting wound healing provided by the present invention. Specific examples have been used to illustrate the principles and implementation methods of the present invention. The descriptions of the above embodiments are only intended to help understand the method and core ideas of the present invention. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of the present invention. Therefore, the content of this specification should not be construed as a limitation of the present invention.
Claims
1. A NO-loaded copper-based metal-organic framework material, characterized in that, The NO-loaded copper-based metal-organic framework material is formed by adsorbing NO onto the copper-based metal-organic framework material. The copper-based metal-organic framework material is formed by periodic coordination assembly of organic ligands and binuclear Cu(II) propeller secondary building units; wherein the general structural formula of the organic ligands is as follows: Wherein, R is selected from –H, –CH3, –NH2 or –N(CH3)2, and X is selected from –C≡C– or –CONH–.
2. The NO-loaded copper-based metal-organic framework material according to claim 1, characterized in that, One of the Cu(II) components in the dual-core Cu(II) propeller secondary building unit is axially coordinated with the pyridine nitrogen donor in the organic ligand structure, and the other Cu(II) component is axially coordinated with a water molecule, forming an open Cu(II) site after desolvation.
3. The NO-loaded copper-based metal-organic framework material according to claim 1, characterized in that, The copper-based metal-organic framework material has a specific surface area of 1300 m². 2 / g-2408 m 2 / g.
4. The NO-loaded copper-based metal-organic framework material according to claim 1, characterized in that, The structural formula of the organic ligand is as follows: 。 5. The NO-loaded copper-based metal-organic framework material according to claim 1, characterized in that, Under conditions of 298 K and 1 bar, the copper-based metal-organic framework material exhibited an adsorption capacity of 3 mmol g for NO. -1 -10 mmol g -1 .
6. The NO-loaded copper-based metal-organic framework material according to claim 1, characterized in that, At 273 K and 1 bar, the copper-based metal-organic framework material adsorbed 10 mmol g of NO. -1 -20 mmol g -1 .
7. A spray formulation for promoting wound healing, characterized in that, The composition of the spray formulation includes: a liquid carrier and the NO-loaded copper-based metal-organic framework material as described in any one of claims 1-6.
8. The spray formulation for promoting wound healing according to claim 7, characterized in that, In the spray formulation for promoting wound healing, the NO-loaded copper-based metal-organic framework material and the liquid carrier are independently packaged in different chambers of the spray device. During use, the NO-loaded copper-based metal-organic framework material and the liquid carrier are mixed and sprayed out by pressing the pump head.
9. The spray formulation for promoting wound healing according to claim 7, characterized in that, The liquid carrier is deionized water.
10. The spray formulation for promoting wound healing according to claim 7, characterized in that, The concentration of the NO-loaded copper-based metal-organic framework material is 50 μg / mL-200 μg / mL.